Internalisasi Nilai Costantini Dalam Pembelajaran Sejarah di Persekolahan Sma Katolik Santu Petrus Pontianak - Veronika Senu; Ika Rahmatika; Andang Firmansyah; Haris Firmansyah (Jurnal Ilmiah Wahana Pendidikan, 2023)
The purpose of this Research was to finding out the history of learning at Santu Petrus Pontianak Catholic High School in the process of planning, implementing, and evaluating internalizing Costantini's values. This research uses descriptive qualitative research. Students, Deputy Head of Curriculum, history teachers, and lesson plans are the sources of this research data. Data collection techniques include data reduction, data presentation, and verification compiled through observation, interviews, and documentation. This is determined from research findings: 1) Costantini's values ​​have not been included in the RPP and syllabus documents. 2) the application of Costantini's values ​​is carried out in the learning process, the Costantini's values ​​contained (Pioneer, Vividerque, Caritas, Humalitas, Cooperente.) 3) the application of Costantini's values ​​is evaluated in the affective domain in the form of peer observation assessments. The values ​​of generosity and cooperation have been applied by students in life 4) students experience difficulties because they are unable to practice the pioneering values, indulgintiae. Meanwhile, teachers face challenges such as not being able to apply Vividiorque's values ​​and not being able to incorporate all of Costantini's values ​​into the history of the learning .